1984
DOI: 10.1172/jci111473
|View full text |Cite
|
Sign up to set email alerts
|

Variations in circulating catecholamines fail to alter human platelet alpha-2-adrenergic receptor number or affinity for [3H]yohimbine or [3H]dihydroergocryptine.

Abstract: Abstract. A series of studies were performed to determine the relationship between physiologic levels of circulating plasma norepinephrine and epinephrine and human platelet alpha-2 binding site number and the affinity (KD) of these sites for antagonist radioligands. In one study, alpha-2-adrenergic binding site number and affinity were compared using both were significantly changed in six normal subjects when plasma norepinephrine levels increased during oral administration of prazosin for 1 wk. Thus, in a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…Per haps this finding is to be expected given the narrow range o f values encountered in the present study. Similar find ing have been reported by others [44], and as indicated above, the literature on this point has become confusing.…”
Section: Relationship O F Plasma Norepinephrine Levels To Other Variasupporting
confidence: 87%
“…Per haps this finding is to be expected given the narrow range o f values encountered in the present study. Similar find ing have been reported by others [44], and as indicated above, the literature on this point has become confusing.…”
Section: Relationship O F Plasma Norepinephrine Levels To Other Variasupporting
confidence: 87%
“…However, several studies indicate that circulating levels of plasma catecholamines do not have important regulatory effects on platelet alpha-2-receptor density (Snavely et al 1982;Pfeifer et al 1984;Egan et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The present results agree with some data from Abrahm et al (14) who found that mean basal plasma norepinephrine levels were not different in the four groups studied (diabetic patients with autonomic neuropathy and orthostatic hypotension (group 1) or without orthostatic hypotension (group 2), diabetic patients without autonomic neuropathy (group 3) and normal subjects (group 4). Moreover, these authors, as did Pfeifer et al (13), indicated that there was no relationship between orthostasis and norepinephrine. In contrast, Hilsted et al (6) did find such a relationship.…”
Section: Discussionmentioning
confidence: 89%
“…In diabetes mellitus, conflicting results were obtained since either no change (13) or a decrease (14) in total platelet « 2 -adrenoceptor number were reported.…”
mentioning
confidence: 99%